1990
DOI: 10.1002/rrr.3450050307
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of benthic macroinvertebrates by minimum flow from a hydroelectric dam

Abstract: The biological consequences of instituting a summer minimum flow from the Conowingo Hydroelectric Dam were investigated by comparing invertebrate abundance in the Susquehanna River during 1980, when flow shutdowns were frequent, to that in 1982, when the minimum flow (142 m3 s-') was maintained. The minimum flow was only maintained from April 15 to September 15, and additional investigations compared invertebrate abundance before and after the minimum flow was terminated in the fall of 1982 and 1983. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…These results are consistent with the findings of Weisberg and Burton (1993), who found that growth rates of white perch (Morone americana) were greater after introducing a minimum environmental flow in the Susquehanna River, because of an increase in prey abundance (Weisberg et al, 1990). Length distributions of New South Wales species do not suggest enhanced growth in unregulated rivers by attainment of greater maximum size than in regulated rivers.…”
Section: Discussionsupporting
confidence: 89%
“…These results are consistent with the findings of Weisberg and Burton (1993), who found that growth rates of white perch (Morone americana) were greater after introducing a minimum environmental flow in the Susquehanna River, because of an increase in prey abundance (Weisberg et al, 1990). Length distributions of New South Wales species do not suggest enhanced growth in unregulated rivers by attainment of greater maximum size than in regulated rivers.…”
Section: Discussionsupporting
confidence: 89%
“…The faunal aspects of these results will be developed and elaborated in another paper, but it can be stressed that the taxa which appeared in this study to be exhibiting the largest changes, such as the Baetidae, Chironomidae, Hydropsychidae, Gammaridae and Simuliidae are also those most frequently mentioned as being significantly affected by reduced or intermittent flow conditions and drought (Ladle & Bass, 1981;Extence, 1981;Wright et al, 1984;Wright & Berrie, 1987;Weisberg et al, 1990). Furthermore, the extensive character of this study and the large variability of faunal responses it highlights, help to place the above single-case studies within the overall picture of a multiplicity of possible trends in faunal responses to reduced flow conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Other pertinent research within the broader arena of instream flows has focused on the delineation of key life history characteristics in terms of ontogenetic shifts in habitat use under natural and induced flow variability (Bardonnet and Gaudin, 1990;Crisp and Hurley, 1991;Bardonnet et al, 1993;Heland et al, 1995), the relationship between flow and macroinvertebrate community dynamics (Statzner, 1988;Gore, 1989;Weisberg et al, 1990;Jowett et al, 1991;Lancaster and Hildrew, 1993) and the importance of trophic level dependencies between macroinvertebrates and fish (Easton and Orth, 1992;Weisberg and Burton, 1993;Roell and Orth, 1994;Filbert and Hawkins, 1995;Bevelhimer, 1996). Efforts employing mechanistic individual based bioenergetics, physical habitat based approaches utilizing population models and multivariate statistical approaches have also produced encouraging results (Jowett, 1992;Addley, 1993;Hill and Grossman, 1993;Jager et al, 1993;Bovee et al, 1994).…”
Section: An Abbreviated Review Of Habitat Modeling Approachesmentioning
confidence: 99%